PENGARUH INOVASI LAYANAN, VIRAL MARKETING, DAN SERTIFIKASI HALAL TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL INTERVENING (STUDI PADA KONSUMEN KEDAI PINARA KOTA SEMARANG) - Lutfia Salma, Nazla; Guritno, Agung (Yayasan Education and Social Center, 2024)
The purpose of this study is to determine the effect of service innovation (X1), viral marketing (X2), halal certification (X3), Purchasing Decisions (Y), and Purchase Interest (Z) on Consumers of Kedai Pinara in Semarang City. The type of research used is quantitative. The data collection method was carried out by distributing questionnaires to Consumers of Kedai Pinara in Semarang City. The sample used was 100 respondents with a non-probability sampling technique. The results of the data analysis that have been carried out show that: (1) Service innovation has a significant positive influence on purchasing decisions. (2) Viral marketing has a positive but insignificant influence on purchasing decisions. (3) Halal certification has a positive and significant influence on purchasing decisions. (4) Purchase interest has a positive but insignificant influence on purchasing decisions. (5) Service innovation has a negative and insignificant effect on purchase intention (6) Viral marketing has a significant positive effect on purchase intention (7) Halal certification has a positive and significant effect on purchase intention (8) Purchase intention is unable to mediate the effect of service innovation on purchase decisions (9) Purchase intention is unable to mediate the effect of viral marketing on purchase decisions (10) Purchase intention is unable to mediate the effect of halal certification on purchase decisions.